Model of Ship Management in Emergencies - Bielić, Toni; Mandžuka, Sadko; Tomas, Vinko (Promet - Traffic&Transportation, 2012)
The paper investigates conditions and circumstances of the occurrence of emergencies during ship exploitation. The concept and different forms of emergencies are defined while conditions of their occurrence are simulated, as well as possible modes of prevention of their occurrence or development. On the basis of the results of the investigation covering 240 professional seamen an appropriate organisational algorithm of participative ship management is defined as foundation for the application of the management algorithm in emergencies. On this basis the method of Risk and Hazard Assessment is applied. Also, the algorithm of Decision Making Process is derived from the related investigations. The proposed algorithm is not based only on the organisational presuppositions of participative management but also on complex human relationships as well as acting in stressful circumstances through all the phases of emergencies. The appropriate decision support system to help decision-makers during the emergencies is described. KEY WORDS: emergencies, algorithm, team work, participative management, hierarchical acting, scenario, communication